Efektivitas Pengelolaan Alokasi Dana Desa Di Desa Rempek Kecamatan Gangga Kabupaten Lombok Utara - Aqma Islamiati; Wahyu Hidayat Riyanto (Program Studi Ekonomi Pembangunan, 2022)
This research aims to find out the Effectiveness of Village Fund Allocation Management (ADD) and to find out the factors that hinder in realize the allocation of village funds in Rempek Village in 2015-2019. The analytical techniques used are descriptive analysis techniques, descriptive analysis techniques using effectiveness techniques and creteria effectiveness ratios. The results showed that the Effectiveness of Village Fund Allocation Management in Rempek Village from 2015-2019 was already in the effective category, effectiveness levels respectively in 2015 (99.66%), 2016 (98.31%), 2017 (96.84%), 2018 (98.40%), 2019 (91.36%). Factors that hinder in realize the allocation of village funds in Rempek village are human resources, facilities supporting inadequate village fund allocation management, and disbursement of late village funds allocation. To overcome obstacles in the realization of village funds allocation can be done with training, budget assessment, and budgeting.